The importance of physical tests in evaluating the level of some physical attributes of soccer players - Khaled, Chennouf; Ali, Adda Ben; Mustapha, Chalal Ismail (International journal of health sciences, 2024)
The study that is in your hands aims to know the importance of physical tests in evaluating the level of some physical attributes of soccer players , and for that we followed the descriptive approach, where the sample of the study amounted to 16 coaches and we used to collect data the questionnaire whose results were analyzed by calculating k2 and percentages, The most important results of the study are that most of the trainers are aware of the importance of physical tests in evaluating some physical characteristics, so we find that they use them Before each stage of training, to know the current level of the player, and thus set the appropriate program. The study reported that the trainers perform physical tests after each stage of training to determine the extent of the development of the level of some qualities, and the results obtained from physical tests help determine the training program and it We recommend conducting periodic tests to measure the level of physical attributes of the players and providing physical tests and modern methods for coaches.